Menilai Ulang Objektivitas Takhrīj al-Ḥadīṡ: Antara Klaim Metode Ilmiah dan Bias Ideologis - Aulia, Annisa Rahma; Harahap, Nurul Amelia; Siregar, Idris; Simangungsong, Liwardha; Salman, Salman (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
This article reassesses the claim of objectivity of takhrīj al-Ḥadīṡ, which has long been positioned as a scientific and neutral methodological procedure in the discipline of ʻulūm al-Ḥadīṡ, by highlighting the problem of ideological bias inherent in its historical and epistemological practices. The research background departs from the dominant assumption that takhrīj functions solely as a value-free sanad and matan verification technique, while several textual indications and scientific practices point to the intervention of mażhab preferences, the hierarchy of narrators’ authority, and the construction of orthodoxy that influence the results of hadith assessments. This study aims to critically evaluate the methodological objectivity of takhrīj al-Ḥadīṡ by examining the epistemic consistency between the claim of scientific procedures and their operational reality in classical hadith literature and contemporary discourse. This study employs a qualitative-critical approach with an epistemological analysis of representative takhrīj works, the rijāl al-Ḥadīṡ, and modern methodological studies, through comparative reading and critical discourse analysis. The results demonstrate a structural tension between technical procedures claimed to be objective—such as assessing the fairness and reliability of narrators—and ideological influences operating through source selection, establishing credibility standards, and legitimizing certain scholarly authorities. These findings indicate that the objectivity of takhrīj is historically and discursively framed, not absolute, thus demanding a more reflective methodological reformulation. The theoretical implications of this study lie in strengthening the critical paradigm in hadith studies, by encouraging the integration of epistemological analysis and ideological criticism to broaden the horizon of a more transparent and accountable hadith methodology.